Physical and psycologycal impact of Hair Removal after a craniotomy - Sarambai, Fris Wilen Weri Brata; SLI, Dina Dewi; Lestari, Retno (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: Hair Removal is the removal of hair in the scalp area to make it easier to mark the incision location and prevent hair contamination in the craniotomy surgical area. Objectives ; This article aims to determine the physical and psychological impact of Hair Removal on patients undergoing craniotomy. Methods: A systematic review was written based on the identification of scientific articles in three databases, Science Direct, PubMed NCBI, and Proquest using the terms Physical, Psychological, Hair Removal, Craniotomy. Neurosurgery The author selected and analyzed using PRISMA based on predetermined inclusion and exclusion criteria. The review obtained from several electronic databases revealed 662 research articles and a total of 11 articles for analysis. Results: The physical impact of using non-standard hair razors causes wounds on the scalp, the striptease hair shaving model has a greater risk of infection during craniotomy operations. The psychological impact of regional hair removal has a negative impact on the patient's body image. The body image scale and anxiety about body shape experienced significant differences between pre and post craniotomy surgery. Conclusions: Hair Removal is still needed to protect the surgical area from hair contamination intraoperatively and make it easier to mark the scalp for incisions during craniotomy surgery. However, there is also a belief that Hair Removal increases the risk of SSI by causing microscopic skin trauma. Regional Hair Removal models can have long-term impacts. This can further affect the patient's body image after the craniotomy procedure